IMPLEMENTASI PROGRAM BERANI SEBAGAI UPAYA INDONESIA DAN UNICEF MENANGANI PERNIKAHAN ANAK DI SULAWESI SELATAN - Simamora, Regina Anggia; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Children are the next generation of the nation whose every right and growth and development must be taken into account by the family and even the state. Child marriage is a phenomenon that is detrimental to children's growth and development and must be addressed immediately. As an initiative to prevent child marriage, the BERANI (Better Sexual and Reproductive Health and Rights for All in Indonesia) Program was formed by UNICEF, UNFPA, Indonesian Government and Canadian Government. Through a qualitative approach using the literature study method, data obtained through literature, reports and official documents related to the BERANI Program and child marriage issue in Indonesia would be analyzed to show implementation and the role of the BERANI Program in preventing the increase in child marriage in South Sulawesi. The findings of this research showed that BERANI Program had successfully implemented its program to prevent child marriage in South Sulawesi and has had an impact on efforts to prevent child marriage. Through results that if found from research, it is hoped that it could provide insight into the implementation of the BERANI program in dealing with child marriage in South Sulawesi in 2018-2023. Keywords: UNICEF, UNFPA, Child marriage, BERANI PROGRAM, Children